Future Challenges of Food Security in Indonesia - Irjayanti, Rahayu; Efendi, Yusuf; Muktiyanto, Didik; Wiyono, Sidik (Graduate School of Universitas Brawijaya, 2026)
Food sustainability is a fundamental pillar of Indonesia’s national development agenda, closely linked to economic resilience, social welfare, and long-term environmental stability. Despite its strategic importance, Indonesia’s current level of food security remains below the global average, indicating persistent structural and systemic challenges. Ensuring future food sustainability therefore requires integrated and adaptive strategies to address multiple pressures, including climate change, shifting consumption patterns, population growth, and volatility in food prices. This study examines the prospects of food security in Indonesia by focusing on three key dimensions: food availability, food access, and food stability. Using a comprehensive analytical approach, the research identifies both the opportunities and constraints within Indonesia’s food system. The findings indicate that Indonesia possesses substantial potential to enhance food sustainability, supported by abundant natural resources, a large agricultural workforce, and growing technological capacity. However, this potential is constrained by uneven productivity, limited access to food for vulnerable populations, and weak mechanisms to stabilize food supply and prices. To overcome these challenges, the study proposes several strategic measures. First, agricultural productivity must be increased through the sustainable application of modern agricultural technologies that are environmentally friendly and climate-resilient. Second, the development of inclusive and sustainable agribusiness models is essential to improve food access, particularly for low-income and rural communities. Third, strengthening food system governance and supply chain management is necessary to ensure price stability and reduce vulnerability to external shocks. These measures must be implemented in an integrated and sustainable manner to secure Indonesia’s long-term food sustainability and resilience. Keywords: changes in consumption habits, climate change, food security, Indonesia, price fluctuations